Application Of Targeted Next-generation Sequencing For The Investigation Of Thalassemia In A Developing Country: A Single Center Experience - Razan Hayati Zulkeflee; Rosnah Bahar; Marne Abdullah; Muhammad Amiro Rasheeq Mohd Radzi; Alina Md Fauzi; Rosline Hassan (MDPI, 2024)
Indexed by WOS/ Scopus